2021
DOI: 10.33448/rsd-v10i3.13073
|View full text |Cite
|
Sign up to set email alerts
|

Leaching from leaves of Sarcomphalus joazeiro and Cenostigma bracteosum stimulate or inhibit the germination of Mimosa caesalpiniifolia?

Abstract: Allelopathy is an ecological mechanism that influences the development of neighboring plants. The objective was to evaluate the allelopathic potential of Cenostigma bracteosum and Sarcomphalus joazeiro on seed germination and initial growth of Mimosa caesalpiniifolia seedlings. Seeds of this species were placed to germinate on paper towel substrate, and then moistened with extracts from dry leaf of S. joazeiro and C. bracteosum at 1.0; 2.5; 5.0 and 10.0% (w.v-1), and control (0.0% - distilled water) at 25 °C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Pacheco et al (2017) [21], using aqueous extract of Pityrocarpa moniliformis observed that although there was no influence of extract concentrations on the germination percentage of Mimosa caesalpiniifolia, observed that the germination process speed decreased sharply as the concentration of leaf extract increased, while the extracts of the fruits provided little significant reduction. Furthermore, Araújo et al (2021) [22] observed deleterious effects of Cenostigma bracteosum leaf extracts, from the concentration of 5%. on seed germination and seedling vigor of Mimosa caesalpiniifolia.…”
Section: Influence Of the Aqueous Extract Of Leaves Of Piptadenia Moniliformis On The Emergence Of Seedlings Of Amburana Cearensismentioning
confidence: 99%
See 1 more Smart Citation
“…Pacheco et al (2017) [21], using aqueous extract of Pityrocarpa moniliformis observed that although there was no influence of extract concentrations on the germination percentage of Mimosa caesalpiniifolia, observed that the germination process speed decreased sharply as the concentration of leaf extract increased, while the extracts of the fruits provided little significant reduction. Furthermore, Araújo et al (2021) [22] observed deleterious effects of Cenostigma bracteosum leaf extracts, from the concentration of 5%. on seed germination and seedling vigor of Mimosa caesalpiniifolia.…”
Section: Influence Of the Aqueous Extract Of Leaves Of Piptadenia Moniliformis On The Emergence Of Seedlings Of Amburana Cearensismentioning
confidence: 99%
“…Including, not only the negative effects of allelopathy, but also the beneficial ones, such as stimulating the germination process and/or the establishment of seedlings. Within this context, it was observed that the germination and vigor of Mimosa caesalpiniifolia seedlings were favored by the extracts of leaves of Sarcomphalus joazeiro [22], denoting a positive influence of allelopathy. [31] highlight the importance of developing research on allelopathic interactions between native tree species in the Caatinga (forest and/or fruit trees), aiming to determine synergistic species that can favor the recovery of degraded areas and sustainable management.…”
Section: Influence Of the Aqueous Extract Of Leaves Of Piptadenia Moniliformis On The Initial Development Of Seedlings Of Amburana Cearenmentioning
confidence: 99%